2003
DOI: 10.1291/hypres.26.193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicardipine on Coronary, Vertebral and Renal Arterial Flows in Patients with Essential Hypertension.

Abstract: used rather than diuretics or β blockers. The acute effects of blood pressure reduction by DPCs on the blood flows in target organs, i.e., the coronary, vertebral and renal artery blood flows in hypertensive patients, have not been well studied.In the present study we measured hemodynamic variables and coronary, vertebral and renal blood flow velocity using a Doppler guidewire and evaluated the acute effect of nicardipine infusion on hemodynamics and on coronary, vertebral and renal artery flows in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…It has also been reported that an ARB reduced vascular microinflammation in essential hypertension (27). However, a CCB was shown to increase basal coronary flow but not hyperemic coronary flow and resulted in reduced CFVR (28). Thus, these previous findings suggest that ARBs and CCBs have quite different effects on CFVR, in agreement with the present study.…”
Section: Changes Of Cfvr By Arbsupporting
confidence: 92%
“…It has also been reported that an ARB reduced vascular microinflammation in essential hypertension (27). However, a CCB was shown to increase basal coronary flow but not hyperemic coronary flow and resulted in reduced CFVR (28). Thus, these previous findings suggest that ARBs and CCBs have quite different effects on CFVR, in agreement with the present study.…”
Section: Changes Of Cfvr By Arbsupporting
confidence: 92%
“…Using a 133 Xe infusion technique, Akopov et al also reported an increase of CBF in hypertensive patients after isradipine treatment, although they showed that treatment with isradipine reduced cerebral perfusion in almost half of the patients with internal carotid artery stenosis (7). Several other studies reported an increase of CBF in hypertensive patients after treatment with calcium channel blockers, as seen with transcranial Doppler (26)(27)(28).…”
Section: Discussionmentioning
confidence: 82%
“…L-type channel antagonists, such as dihydropyridines, phenylalkylamines, and benzothiazepines, are used for treatment of hypertension and angina pectoris (4,5,7,8,28,29). The dihydropyridine, phenylalkylamine, and benzothiazepine binding sites appear to encompass separate but partially overlapping regions located within domains III and IV (30 -32).…”
Section: Discussionmentioning
confidence: 99%